Automated heat pump heating system using nontraditional energy sources - Olishevskiy, I.; Gusev, O.Yu.; Isakova, M. L. (Видавництво НТУ "ДП", 2021)
Heating systems are one of the most expensive to use fuel and energy resources (not less than 30% of total consumption). This leads to a constant search for various solutions to increase the energy efficiency of heating systems. In addition, air conditioning systems have become widespread. A large amount of thermal energy, calculated in millions of GJ, is wasted into the environment through the outdoor units of air conditioners. This leads to the search for new ways to increase the energy efficiency of heating and air conditioning systems.
Keywords: автоматизована система опалення; тепловий насос; нетрадиційні джерела енергії